Can we estimate the causal effects of diet and sedentary behavior on schoolchildren's overweight/obesity from observational studies? - Emil Kupek (Open Exploration Publishing Inc., 2023)
Aim: To investigate the causal impact of diet and sedentary behavior on Brazilian schoolchildren's overweight/obesity using the data from observational studies. Methods: Annual cross-sectional nutritional surveys over the 2013-2015 period, with 26,712 children old 7-12 years in Florianópolis, Brazil, provided the data for this analysis. The surveys applied an online previous-day recall questionnaire on food intake and physical/sedentary activities. Outcome measures were overweight/obesity, whereas exposure variables were daily frequencies of consuming sugary drinks and ultra-processed foods, the total number of dietary items consumed and the total number of sedentary activities per day, and consuming breakfast, mid-morning snacks, lunch, afternoon snack, dinner, and evening snack. Control variables included child age, sex, family income, school shift, survey year, day of the week the questionnaire refers to, metabolic equivalents (METs) of physical activities (PAs), and the quality of dietary and PA reports. Causal effects were estimated by augmented inverse probability weighting. Results: Daily consumption of sugary drinks, eating ten or more foods, and engaging in three or more sedentary behaviors per day significantly increased the odds ratios (ORs) of being overweight/obese in the range of 3-24% compared to the reference, with 95% confidence intervals in the range of 1-32%. Among 19 ORs with P-value ≤ 0.05, only 3 exceeded 10%. Conclusions: Under certain conditions, not uncommon in large-scale monitoring and surveillance studies, it is possible to evaluate the causal effects of diet and sedentary activities on overweight/obesity. Daily consumption of sugar-sweetened beverages, eating ten or more foods, skipping breakfast, and engaging in three or more sedentary behaviors per day significantly increased the odds of being overweight/obese.